Moist-heat induced interfacial co-assembly of κ-carrageenan and soy lecithin: A chemical-crosslinker-free paradigm for physically stable Pickering emulsion - Han Liu; Chengbin Sun; Xiaoyan Wu; Guimei Liu; Bin Yu; Xuemin Kang; Zisong Li; Zhengmin Li; Haiteng Tao; Bo Cui (Food Hydrocolloids, 2026)

Atomic site design and hierarchical porosity: Fe-N-C catalysts for high-efficiency oxygen depolarized cathodes - Shengnan Li; Chengbin Wang; Lichen Zhang; Kaicai Fan; Zumin Wang; Yu-Cheng Shao; Porun Liu; Qingxu Sun; Lingbo Zong (Chemical Engineering Journal, 2026)

Transplantation of Skin-Derived Precursor Schwann Cells Ameliorates Secondary Brain Injury after ICH in Mice by Activating the PI3K/AKT/FOXO3a Signaling Pathway - Yuqian Tang; Yan Song; Qiuwen Sun; Muyuan Tong; Yejing Zhang; Yan Chen; Junyi Sha; Chengbin Xue; Jiabing Shen; Aihong Li (Translational Stroke Research, 2026)

Effect of roasting treatment on flavor and quality of fragrant corn oil - Guohao Sun; Shangde Sun; Hao Zhang; Yaoyao Zhang; Chengbin Sun; Dami Li; Talha Ashfaq; Xuze Zhang (Food Chemistry, 2025)

Fatigue crack propagation pattern analysis of horizontal-axis tidal energy turbine - Xiaocui Chen; Song Guo; Chengbin Du; Yuquan Zhang; Liguo Sun (Ocean Engineering, 2025)

Efficient and stable electro-Fenton treatment of antibiotics-containing wastewater over NiFe bimetal atom catalyst via flow-through micro-nanoscale spatial confinement system - Danyu Zhang; Yarong Chen; Yuchen Wang; Hao Zhang; Haifang Tang; Xuhui Sun; Qingquan Liu; Chengbin Liu (Journal of Hazardous Materials, 2025)

Prolonging the operation of lithium metal batteries by inhibiting corrosion with a polymer binder coating - Lanhang Li; Hongyan Li; Qingyue Han; Yiyu Huang; Tianyu Wang; Lei Sun; Hongxian Zhang; Ziyue Zhang; Lijing Yan; Chengbin Jin; Ouwei Sheng (Chemical Engineering Journal, 2025)

Integrated Transcriptomic and Metabolomic Analysis Reveals the Molecular Mechanisms Involved in the Adaptations of Mandarin Fish (Siniperca chuatsi) to Compound Feed - Yunyun Yan; Yuan Zhang; Junjian Dong; Fubao Wang; Hetong Zhang; Fengying Gao; Xing Ye; Chengbin Wu; Chengfei Sun (Fishes, 2025)
Siniperca chuatsi is an important high-quality freshwater aquaculture species in China. In nature, it feeds exclusively on live food. In this study, domesticated juvenile S. chuatsi were divided into three groups and fed live food (group L), compound feed (group C), or a mixed diet (group M) for three months to investigate the molecular mechanisms underlying adaptation to compound feed. Histopathological examination revealed that compound feed consumption induced looser liver cell arrangement, hepatocyte morphological irregularities, and vacuolization. A total of 1033 and 1428 differentially expressed genes (DEGs), and 187 and 184 differential metabolites (DMs), were identified in the C vs. L and C vs. M groups, respectively. Transcriptomic analysis revealed that the significantly and commonly enriched metabolic pathways shared by both comparison groups were predominantly involved in amino acid, carbohydrate, and lipid metabolisms. Metabolomic analysis demonstrated that the significantly and commonly enriched metabolic pathways shared by both comparison groups were the arachidonic acid metabolism, linoleic acid metabolism, oxidative phosphorylation, and PPAR signalling pathways. Integrated omics analysis showed that the PPAR signalling pathway was the only significantly co-enriched pathway across both omics datasets. This study provides new insights into the molecular mechanisms of compound feed adaptation and provides theoretical support for selecting feed traits in S. chuatsi.

Development of high internal phase Pickering emulsions utilizing ternary complexes of octenyl succinate millet starch/chitosan hydrochloride-EGCG particles and their applications in 3D printing - Yuting Ji; Shan Gao; Mengyu Li; Yikun Xu; Chengbin Sun; Hanxue Hou; Yangyong Dai; Wentao Wang (Food Chemistry, 2025)

Effect of silver nanoparticles on biological nitrogen removal in sequential batch wastewater treatment process: Microbial communities, functional genes, and interactions - Yuliang Zhu; Hui Zhang; Hongwei Sun; Yan Zhang; Lei Yang; Chengbin Liu; Xinyi Yang; Yucan Liu (Journal of Water Process Engineering, 2025)

Integrating adsorption and in-situ catalytic regeneration on N doped carbon aerogel for sustainable continuous-flow water treatment - Chengbin Sun; Lingjie Song; Xiaoli Dong; Xiufang Zhang; Guanlong Wang (Environmental Research, 2025)

Effects of Different Light Spectra on Oxidative Stress and Nutritional Quality of the Fish Plectropomus leopardus - Wensheng Li; Zheng Zhang; Baoliang Liu; Yingying Fang; Shuquan Cao; Wenyang Li; Yan Sun; Chengbin He; Chuanxin Zhang; Fan Fei (Fishes, 2024)
This study investigated the impacts of light spectra on oxidative stress and nutrient quality of the fish Plectropomus leopardus in indoor recirculating aquaculture systems. The fish (100 g ± 0.45 g [wet weight]) were cultures in five different light spectra (full-spectrum (400–800 nm), blue (450 nm), green (530 nm), red (630 nm), and dark) for 60 days. After experimentation, blood and muscle tissue were collected and analyzed for biochemical variables and nutritional quality. We demonstrated that the total cholesterol, triglycerides activities of P. leopardus in the dark groups were substantially elevated, relative to other groups (p

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Inspired by human olfactory system: Deep-learning-assisted portable chemo-responsive dye-based odor sensor array for the rapid sensing of shrimp and fish freshness - Chengbin Jiang; Alan J.X. Guo; Yuwen Li; Yufan Wang; Jianfeng Sun; Zhizhou Chen; Xin Chen; Qianyun Ma (Chemical Engineering Journal, 2024)

Growth arrest and DNA damage-inducible 45 ab gene targeted by miR-20b-5p executes the inflammation and apoptosis by regulating MAPK and NF-κB pathways in black rockfish - Chengbin Gao; Peng Sun; Xin Cai; Le Ma; Ying Zhu; Min Cao; Chao Li (Aquaculture, 2024)

Turbot (Scophthalmus maximus L.) occludin gene performs the anti-inflammatory function in the intestine via the regulations by miR-140-3p in the NF-κB pathway - Xin Cai; Peng Sun; Chengbin Gao; Ting Xue; Le Ma; Chao Li (Aquaculture, 2024)

Accumulation characteristics of metals in human breast milk and association with dietary intake in northeastern China - Chengbin Zhang; Yun Luo; Shuai Sun; Tian Tian; Meiwen Zhu; Zia Ahmad; Jiajia Yang; Jing Jin; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Theoretical study on the potential environmental and ecological risk of 4-ethylphenol induced by hydroxyl radical - Ruiqing Zhang; Chengbin Yin; Hui Li; Xiaomin Sun; Yan Zhao (Environmental Pollution, 2024)

Geographical features and development models of estuarine cities - Mingxing Chen; Yue Xian; Yaohuan Huang; Zhigang Sun; Chengbin Wu (Journal of Geographical Sciences, 2024)

Systematic analysis of circRNA-related ceRNA networks of black rockfish (Sebastes schlegelii) in response to Aeromonas salmonicides infection - Chengbin Gao; Xin Cai; Le Ma; Peng Sun; Chao Li (Fish & Shellfish Immunology, 2023)

Isosteviol improves cardiac function and promotes angiogenesis after myocardial infarction in rats - Fei Liu; Laisi Song; Zhiqiang Lu; Tingwei Sun; Jingwen Lun; Chengbin Zhou; Xiouou Sun; Wen Tan; Haishan Zhao (Cell and Tissue Research, 2022)

Regulatory effects of antitumor agent matrine on FOXO and PI3K-AKT pathway in castration-resistant prostate cancer cells - Qi Li; Hai Huang; Zheng He; Yi Sun; Yufeng Tang; Xiaohong Shang; Chengbin Wang (Science China Life Sciences, 2018)